Immune-antioxidant trait, Aeromonas veronii resistance, growth, intestinal architecture, and splenic cytokines expression of Cyprinus carpio fed Prunus armeniaca kernel-enriched diets. Issue 124 (May 2022) - Mahboub, Heba H.; Faggio, Caterina; Hendam, Basma M.; Algharib, Samah Attia; Alkafafy, Mohamed; Abo Hashem, Marwa; Mahmoud, Yasmina K.; Khamis, Tarek; Abdel-Ghany, Heba M.; Masoud, Shimaa R.; Abdel Rahman, Afaf N.
Abstract: Currently, the intervention of plant by-products in the fish diet has gained tremendous attention owing to the economic and high nutritious value. The current study is a pioneer attempt to incorporate the apricot, Prunus armeniaca kernel powder (PAKP) into the Common carp, Cyprinus carpio diets, and assess its efficacy on growth, digestion, intestinal morphology, immunity, antioxidant capacity, and splenic cytokines expression, besides the antibacterial role against Aeromonas veronii infection. Apparently healthy fish (N = 120) with an initial body weight of 24.76 ± 0.03g were allotted in 12 glass aquaria (60 L) and randomly distributed into four groups (triplicates, 10 fish/aquarium). The control group (PAKP0) was fed a basal diet without additives. The second, third, and fourth groups were provided PAKP diets with various concentrations (2.5 (PAKP2.5), 5 (PAKP5), and 10 g kg −1 (PAKP10)) respectively. After 60 days (feeding trial), sub-samples of the fish (12 fish/group) were intraperitoneally injected with 1 × 10 7  CFU mL −1 of A. veronii . Results revealed that body weight gain, feed conversion ratio, and specific growth rates were significantly augmented in the PAKP10 group in comparison to the other groups. The dietary inclusion of PAKP at all concentrations boosted the digestive capacity and maintained the intestinal morphology (average villus length, villus width, and goblet cells count) with a marked improvement in PAKP10. Moreover, fish fed on PAKP10 followed by PAKP5 then PAKP2.5 diets had noticeably elevated values of immunological biomarkers (IgM, antiprotease, and lysozyme activity) and antioxidant capabilities (the total antioxidant capacity, superoxide dismutase, and reduced glutathione) as well as significant up-regulation of immune and antioxidant-related genes ( TGF-β2, TLR-2, TNF-α, IL-10, SOD, GPx, and GSS ). Fourteen days post-infection with A. veronii, the highest relative percentage survival of fish was observed in PAKP10 (83.33%), followed by PAKP5 (66.67%), and PAKP2.5 (50%). Our results indicated that a dietary intervention with PAKP could promise growth, digestion, immunity, and protect C. carpio against A. veronii infection in a dose-dependent manner. This offers a framework for future application of such seeds as a growth promotor, immune-stimulant, and antioxidant, besides an alternative cheap therapeutic antibacterial agent for sustaining the aquaculture industry. Highlights: Prunus armeniaca kernel powder (PAKP) diet inclusion improved growth performance of C. carpio. Diet supplement with PAKP enhanced digestion and intestinal architecture. Dietary PAKP induced an immune-antioxidant indices and genes expression augmentation. PAKP enhanced the resistance against Aeromonas veronii infection in C. carpio.